Determinants of Destination Loyalty Among Jatijajar Cave Tourists: A Sor Theory Perspective - Ryska Amelia Sabyla; Yadi Ernawadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the effects of legend storytelling, esthetic, education, and natural landscape on destination loyalty through destination attachment among Jatijajar Cave tourists. A survey method was employed involving respondents who had visited Jatijajar Cave . The data were analyzed using SEM with SmartPLS version 3.0. SOR theory served as the theoretical foundation for developing the conceptual model by modifying the independent variables from previous research to better suit the characteristics of a cultural heritage tourist destination. The results indicate that legend storytelling, esthetic, education, and natural landscape positively affect destination loyalty through destination attachment. The findings are expected to assist the management of Jatijajar Cave in prioritizing education, followed by natural landscape, esthetic, and legend storytelling. The relatively smaller influence of legend storytelling and esthetic suggests the need for further research by adding other relevant variables that can be hypothesized as antecedents of destination attachment at a higher level. Therefore, future research is recommended to include additional relevant variables in the conceptual model.